Serum Creatinine and Urine Microalbumin Level in Hypertensive and Non hypertensive Patients. - Joshi, Keshab Raj; Gautam, Ashish; Pandeya, Dipendra Raj; Poudel, Keshab (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Hypertension is one of the most common cardiovascular disorders, more likely to accelerateatherosclerosis causing cardiovascular complications and benign arteriolar nephrosclerosis for an extendedperiod of time may manifest as a mild to moderate elevation of serum creatinine and/or microalbuminuria. Methods: The present study was carried out on total 100 subjects. Which were divided into two groups. Firstgroup of experimental group consist of 50 subjects with known Hypertensive Subjects. Another group is controlgroup consist of 50 Non-Hypertensive Subjects with no present and past family history of hypertension. Results: The serum creatinine and microalbuminuria were estimated, compared and correlated in hypertensivecase group with healthy normotensive group. In case group there was signiÞ cantly elevated urine microalbuminand serum creatinine levels when compared to controls and also signiÞ cant positive correlation betweenserum creatinine and urine microalbumin levels in case group (hypertensive) as compared to control (nonhypertensive) group Conclusions: In the present study it has concluded that in Hypertensive patients serum creatinine, urinemicroalbumin is stastistically elevated in subjects group when compared to the control group. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12923